IDENTIDADES DOCENTES ENTRE MUNDOS DISCURSIVOS EM DISPUTA: FORMAÇÃO DO PROFESSOR, LETRAMENTOS E DESENVOLVIMENTO. - Lopes Nascimento, Elvira; Baracat De Grande, Paula (Trabalhos em Lingüística Aplicada)
This paper aims to analyze the identity construction, negotiation and disputation in the entrance process of a teacher of the basic school in a Professional Master 's course. For this purpose, we selected excerpts from a self-confrontation session held after the completion of the Master course. We start from the theoretical framework of Sociodiscursive Interactionism and Didactic Engineering of the School of Geneva, perspectives studied by the teacher participating in the research for the writing of her master's dissertation. For the identities analysis, we mobilize the sociocultural perspective of Literacy Studies, the concept of identity as multiple, fluid and constructed discursively, and the concept of social voices, to understand if the process of constructing identities in disputed discursive worlds - the school and university - result in the teacher's professional development. The results highlight the importance of considering teacher continuing education as an identity process, which involves a construction of what it is to be a teacher in the contemporary world.